Peningkatan Literasi Dan Numerasi Siswa Kelas IV Melalui Program Pojok Baca di SDN Aimitat, Desa Urungpigang, Kecamatan Wailiti - Karmila Karmila; Winda Winda; Ayuni Ayuni; Rimasi Rimasi (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
This research aims to increase students' Numeracy Literacy through a reading corner. This research was motivated by the low motivation of students in numeracy literacy at SDN Aimitat. Therefore, one of the first steps taken was to create a "Reading Corner" program, namely providing reading books according to class level to students who were accompanied directly by the teacher to ensure routine reading activities with students run well. This research is a qualitative descriptive research, with the research subjects being fourth grade students. Based on the results of the study, data was found that the implementation of a reading corner can increase numeracy literacy in fourth grade students at SDN Aimitat.